Mechanisms for ensuring state regulation of the logistics services market in the context of sustainable development - Samoilenko, Bohdan; Starodubtseva, Liubov; Dluhopolska, Tetiana (Innovatio Press Wydawnictwo Naukowe Lubelskiej Akademii WSEI, 2024)
The logistics sector is one of the critical elements of the economy, which significantly influences productivity, distribution of goods and services, and the country’s overall competitiveness. In Ukraine, as well as in many other countries, there is a steady growth in the demand for logistics services driven by internal and external factors. However, for this market to function efficiently, clear, and transparent state regulatory mechanisms must balance interests between the state, business, and consumers. The current state regulation of the logistics services market in Ukraine has such problems as an imperfect legal framework, insufficient institutional support, lack of transparency, and poor coordination with other sectors. Therefore, it is proposed that a collaborative approach be adopted to consider certain aspects that will contribute to more effective regulation of the logistics market, ensuring that all stakeholders’ voices are heard and their interests are taken into account.
Keywords: Mechanisms; for ensuring; state regulation; of the logistics; services market; in the context; of sustainable development